4E multi-objective optimization of cold electricity co-generation system based on supercritical CO2 Brayton cycle. (1st May 2023) - Wang, Yiming; Xie, Gongnan
Highlights: Multi-objective optimization is performed based on energy, exergy, economy and environment (4E). The selection reliability of TOPSIS, MO and LINMAP decision methods are compared. Cycle performance under two refrigeration conditions are analyzed qualitatively and quantitatively. Performance of PCHE with different cycle layouts is analyzed before and after optimization. Abstract: Reheat Brayton cycle has advantages of compact layout and high efficiency, and heat recovery from cooler in Brayton cycle by ammonia absorption refrigeration cycle can achieve efficient cold electricity co-generation. In this paper, evaluation models based on energy, exergy, economy and environment (4E) are established and multi-objective optimization are carried out for combined cycle. The reliability and accuracy of TOPSIS, MO and LINMAP decision methods are analyzed. Cycle performance, economy and environment benefits are compared and analyzed under two refrigeration conditions before and after optimization. Temperature difference distribution of printed circuit heat exchanger under different cycle layouts is analyzed. The results show that TOPSIS and LINMAP are reliable, and MO is not suitable for selection of optimum points in Pareto diagram; after optimization, economic and environment costs of top cycle are reduced by 11.21% and 6.68%, refrigeration capacity of bottom cycle under two refrigeration conditions is improved by 28.75% and 15.46%, and economic costs are reduced by 28.3% and 3.7%; for combined cycle, thermal efficiency is increased by 1.11% on average, total investment cost is reduced by 16.21% on average, overall performance of combined cycle is significantly improved; compared with basic and reheat cycle before optimization, temperature difference in high temperature section of recuperator is significantly reduced in reheat Brayton cycle after optimization, which is good for reducing exergy loss and heat stress, helping to match high temperature and pressure environment of top cycle; temperature difference in low temperature section of subcooler is increased in bottom cycle after optimization, which helps to reduce heat exchanger volume and improve compactness.